2012
DOI: 10.3386/w18661
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Equilibrium Models of Labor Market Sorting

Abstract: Does the market allocate the right workers to the right jobs? Since observable (to economists) variables account for only a small fraction of the wage variance in the data, to answer this question it is essential to study assortative matching between employers and employees based on their unobserved characteristics. This paper enables this line of research. We show theoretically that all parameters of the classic model of sorting based on absolute advantage in Becker (1973) with search frictions can be identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 14 publications
(52 reference statements)
4
75
0
Order By: Relevance
“…2 Many structural models proposed in the literature build on Becker (1973). Examples are Lopes de Melo (2018), Lise, Meghir, and Robin (2016), Bagger and Lentz (2014), Hagedorn, Law, and Manovskii (2017), and Lamadon, Lise, Meghir, and Robin (2013). per firm tends to be small, which creates an incidental parameter bias in estimation. 3 In such environments, reducing the number of classes can alleviate small-sample biases.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many structural models proposed in the literature build on Becker (1973). Examples are Lopes de Melo (2018), Lise, Meghir, and Robin (2016), Bagger and Lentz (2014), Hagedorn, Law, and Manovskii (2017), and Lamadon, Lise, Meghir, and Robin (2013). per firm tends to be small, which creates an incidental parameter bias in estimation. 3 In such environments, reducing the number of classes can alleviate small-sample biases.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers that analyse matching in Germany focus exclusively on West Germany, see Alda et al (2009), Card et al (2013 or Hagedorn et al (2017). Even though Destefanis and Fonseca (2007) estimate matching efficiency exploiting the relation between the unemployment and the vacancy rate, the authors find significant differences between the North and the South of Italy.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent structural approaches, such asHagedorn et al (2017), seek to estimate both workers' and vacancies' productivities in a unified framework Bagger and Lentz (2014). andLise et al (2016) adopt on-the-job search and derive productivity proxies from observed worker flows between firms Bartolucci et al (2015).…”
mentioning
confidence: 99%
“…However, as noted by Eeckhout and Kircher (2011), these fixed effects need not be connected to the underlying firm and worker types. Hagedorn et al (2017) proposed an estimator of F , but its asymptotic properties are unknown. To our knowledge, no test of PAM or supermodularity of F is available.…”
Section: Delivering Economic Implicationsmentioning
confidence: 99%